The economics of infrastructure finance: Public-private partnerships versus public provision - Eduardo M. R. A. Engel; Ronald D. Fischer; Alexander Galetovic (EIB Papers, 2010)
We examine the economics of infrastructure finance, focusing on public provision and Public-Private Partnerships (PPPs). We show that project finance is appropriate for PPP projects, because there are few economies of scope and because assets are project specific. Furthermore, we suggest that the higher cost of finance of PPPs is not an argument in favour of public provision, since it appears to reflect the combination of deficient contract design and the cost-cutting incentives embedded in PPPs. Thus, in the case of a correctly designed PPP contract, the higher cost of capital may be the price to pay for the efficiency advantages of PPPs. We also examine the role of government activities in PPP financing (e.g. revenue guarantees, renegotiations) and their consequences. Finally, we discuss how to include PPPs, revenue guarantees and the results of PPP contract renegotiation in the government balance sheet.
Keywords: 330